In vitro evaluation of glutathione implementation on oxidative dna damage and oxidant status in high glucose conditions - Fatmagul Yur; Semiha Dede; Sedat Cetin; Mehmet Taspinar; Ayse Usta (Eurasian Journal of Veterinary Sciences)
Aim: This study aimed to show the effects of glutathione, recognized by its antioxidant specialties, on the potential DNA damage (8-hydroxy-2- deoxyguanosine) and the antioxidant system changes upon its implementation in BHK-21 cells cultured with high glucose. Materials and Methods: BHK-21 cell line was regularly surpassed in vitro conditions (5% FBS, 10% horse serum, 1% L-Glutamine, 1% penicillin/ streptomycin in RPMI 1640 medium, and 5% CO2 and 95% humidity and 37ºC) incubated. The control group determined glucose's IC50 value based on the viability tests executed on MTT cells. Cells were seeded in plates as each would have 2x106 cells. The control, the test, and the crossbreed test (glucose; (285 mM), glutathione (250 &micro ,M)) groups were prepared. After 24 hours of incubation, trypsinized cells were designed for analysis through vitrification. In the lysate of the cell culture that was procured, Oxidative DNA damage, TAS, TSO, and OSI were measured by the spectrophotometric system with ELISA. Results: It was observed that 8-OHdG levels increased significantly with glucose application. Moreover, the increase in the HG+GSH group was more significant when compared to the control group (p≤0.05). No difference with the control group was found only in the group where GSH was applied. As for TAS, whereas any difference was observed in GSH used groups, the increase in the HG+GSH group was significant compared to the control group (p≤0.05). that were the same as the control group. TOS and OSI considerably increased in HG + GSH implemented groups as to the control group (p≤0.05). Conclusion: According to the results, no protective impacts of glutathione at the cellular level in the doses mentioned above were observed on high-dose glucose implemented cells. On the other hand, it was revealed that the applied amounts of glutathione in the process did not cause any toxic effects.